Strategi Pengembangan Usaha Pelatihan Hidroponik Di Kota Bogor - Syuja' Hakim, Muhammad Alief; M. Baga, Lukman; Tinaprilla, Netti (Forum Agribisnis, 2024)
Hydroponics is a method of cultivating plants without soil that is popular with Indonesian people. Its spread in Indonesia is supported by information openness via the internet and social media. Internet users reaching 77.2% have created a demand for hydroponic training. The urgency of training services is needed because hydroponic cultivation requires special skills. In the city of Bogor, there are business units that provide hydroponic training with limited face-to-face services which are very vulnerable to schedule limitations and social restriction policies by the government. The aim of this research is to formulate a strategy for developing a hydroponics training business in the city of Bogor. The approach uses qualitative methods with the Business Model Canvas framework to map digitalization adaptation and describe existing business models. Alternative strategies are formulated using SWOT analysis which combines internal strategic issues in the form of strengths and weaknesses with external strategic issues in the form of opportunities and threats. The formulated alternative strategy is implemented into the prototype canvas business model. Customer Response Index analysis is carried out to support SWOT analysis to obtain input based on responses from consumers. The research results found that digital adaptation was limited to business model marketing channels. Strength strategic issues lie in segmentation based on demand, service flexibility, and digital marketing adaptation. The weakness issue is dependence on one product and dependence on business partners. Strategic issues of opportunity are opportunities for product diversification, new partnerships, and conversion of training into digital products. The strategic threat issue is the opportunistic risk of business partners. The formulation of an alternative strategy recommends diversifying service products by adding services that are still in the hydroponics business line.